Perbandingan Algoritma K-Nearest Neighbor dan Naive Bayes Untuk Klasifikasi Status Penjualan Furniture dengan Data Historis - Sucahyo, Bangkit Dwi; Riskiono, Sampurna Dadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to evaluate the performance of two machine learning classification methods, K-Nearest Neighbor (KNN) and Naive Bayes, in predicting the sales status of furniture products at CV. Surya Gemilang. The data used comes from previous sales records and includes details such as product category, product name, price, sales amount, revenue, and sales status, which are labeled